Conductive complex dispersion and production method therefor, capacitor and production method therefor, and conductive laminate and production method therefor
Patent Information
- Application Number
- JP2023135158
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-23
- Publication Date
- 2025-03-07
AI Technical Summary
【0007】 本発明の導電性複合体分散液は、耐熱性や耐電圧が高性能のキャパシタの製造に適している。この性質は、キャパシタの製造だけでなく、基材の上に導電層が積層された導電性積層体の製造にも適している。
Smart Images

Figure 2025030132000002 
Figure 2025030132000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive composite dispersion containing a π-conjugated conductive polymer and a polyanion, a capacitor, and a conductive laminate. [Background technology]
[0002] A π-conjugated conductive polymer, whose main chain is composed of a π-conjugated system, forms a conductive complex by doping with a polyanion having an anionic group, and becomes dispersible in water. A method for producing a capacitor has been disclosed in which a paint made from a conductive composite dispersion liquid containing a conductive composite is applied to a dielectric layer provided on the surface of an anode made of a valve metal, the paint is dried to form a solid electrolyte layer, and a cathode is placed opposite the solid electrolyte layer (e.g., Patent Document 1). According to this disclosure, the capacitor performance is improved by including a specific unsaturated aliphatic alcohol compound in the paint. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2022-071400 Summary of the Invention [Problem to be solved by the invention]
[0004] Since the environment during the manufacturing and use of capacitors can become very hot, capacitors are required to have sufficient heat resistance and high voltage resistance.
[0005] The present invention provides a conductive composite dispersion suitable for producing high performance capacitors. [Means for solving the problem]
[0006] [1] A conductive complex containing a π-conjugated conductive polymer and a polyanion, water, a sugar alcohol or glucose having 4 to 7 carbon atoms and 3 to 7 hydroxyl groups in the molecule, and a polymer compound different from the conductive complex; The conductive complex dispersion has a mass ratio, expressed as A / B, of the content A of the sugar alcohol and glucose to the content B of the polymer compound, of 0.3 or more and less than 1.5. [2] The conductive complex dispersion liquid according to [1], wherein the sugar alcohol contains at least one of sorbitol, mannitol, erythritol, and pentaerythritol. [3] The conductive composite dispersion liquid according to [1] or [2], wherein the polymer compound contains at least one of polyethylene glycol and polypropylene glycol. [4] The conductive composite dispersion liquid according to any one of [1] to [3], further comprising an organic solvent having a boiling point of 150° C. or higher at 1 atmospheric pressure. [5] The π-conjugated conductive polymer is poly(3,4-ethylenedioxythiophene), or the polyanion is polystyrenesulfonic acid, or The conductive composite dispersion liquid according to any one of [1] to [4], wherein the π-conjugated conductive polymer is poly(3,4-ethylenedioxythiophene) and the polyanion is polystyrenesulfonic acid. [6] A method for producing a conductive complex dispersion, comprising: mixing a conductive complex consisting of a π-conjugated conductive polymer and a polyanion, water, a sugar alcohol or glucose having 4 to 7 carbon atoms and 3 to 7 hydroxyl groups in the molecule, and a polymer compound different from the conductive complex, to obtain a conductive complex dispersion in which the mass ratio, expressed as A / B, of the content A of the sugar alcohol and glucose to the content B of the polymer compound is 0.3 or more and less than 1.5. [7] An electrochemical cell comprising: an anode made of a porous body of a valve metal; a dielectric layer made of an oxide of the valve metal; a cathode made of a conductive material provided on the dielectric layer opposite the anode; and a solid electrolyte layer formed between the dielectric layer and the cathode; A capacitor, wherein the solid electrolyte layer is a cured product of the conductive composite dispersion liquid according to any one of [1] to [5]. [8] A method for producing a capacitor, comprising the steps of applying the conductive composite dispersion liquid according to any one of [1] to [5] to a surface of a dielectric layer formed on the surface of an anode made of a porous valve metal, and drying the applied conductive composite dispersion liquid to form a solid electrolyte. [9] A substrate and a conductive layer formed on at least a portion of the surface of the substrate, The conductive layer is a cured product of the conductive composite dispersion according to any one of [1] to [5].
[10] A method for producing a conductive laminate, comprising the steps of applying the conductive composite dispersion liquid according to any one of [1] to [5] to at least a part of a surface of a substrate, and drying the applied coating to form a conductive layer.
[11] The conductive complex dispersion liquid according to any one of [1] to [5], wherein the sugar alcohol has a non-cyclic structure.
[12] The conductive composite dispersion liquid according to any one of [1] to [5] and
[11] , wherein the polymer compound contains a water-soluble polymer compound.
[13] The conductive composite dispersion liquid according to any one of [1] to [5],
[11] and
[12] , wherein the polymer compound has an average molecular weight of 1,000 or less.
[14] The conductive composite dispersion according to any one of [1] to [5] and
[11] to
[13] , which may further contain a neutralizing agent. Effect of the Invention
[0007] The conductive composite dispersion of the present invention is suitable for the production of a capacitor having high heat resistance and voltage resistance. These properties are suitable not only for the production of a capacitor but also for the production of a conductive laminate in which a conductive layer is laminated on a substrate.
[0008] This invention is believed to contribute to SDGs Goal 12, "Responsible Consumption and Production."
[0009] In this specification and claims, the lower limit and upper limit of a numerical range indicated with "to" are included in the numerical range. [Brief description of the drawings]
[0010] [Figure 1] FIG. 2 is a cross-sectional view illustrating one embodiment of a capacitor. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] ≪Conductive composite dispersion liquid≫ A first aspect of the present invention is a conductive complex dispersion liquid comprising a conductive complex containing a π-conjugated conductive polymer and a polyanion, water, a specific sugar alcohol or glucose, and a polymer compound different from the conductive complex.
[0012] <Conductive composite> The conductive complex of this embodiment includes a π-conjugated conductive polymer and a polyanion. The polyanion in the conductive complex is doped into the π-conjugated conductive polymer to form a conductive complex having electrical conductivity. In the polyanion, only a part of the anionic groups is doped into the π-conjugated conductive polymer, and the polyanion has excess anionic groups that are not involved in the doping. Since the excess anionic groups are hydrophilic groups, the conductive complex has water dispersibility.
[0013] (π-conjugated conductive polymer) The π-conjugated conductive polymer may be an organic polymer whose main chain is composed of a π-conjugated system, and examples thereof include polypyrrole-based conductive polymers, polythiophene-based conductive polymers, polyacetylene-based conductive polymers, polyphenylene-based conductive polymers, polyphenylenevinylene-based conductive polymers, polyaniline-based conductive polymers, polyacene-based conductive polymers, polythiophenevinylene-based conductive polymers, and copolymers thereof. From the viewpoint of stability in air, polypyrrole-based conductive polymers, polythiophenes, and polyaniline-based conductive polymers are preferred, and from the viewpoint of transparency, polythiophene-based conductive polymers are more preferred.
[0014] Polythiophene-based conductive polymers include polythiophene, poly(3-methylthiophene), poly(3-ethylthiophene), poly(3-propylthiophene), poly(3-butylthiophene), poly(3-hexylthiophene), poly(3-heptylthiophene), poly(3-octylthiophene), poly(3-decylthiophene), poly(3-dodecylthiophene), poly(3-octadecylthiophene), poly(3-bromothiophene), poly(3-chlorothiophene), and poly(3-iodothiophene). thiophene), poly(3-cyanothiophene), poly(3-phenylthiophene), poly(3,4-dimethylthiophene), poly(3,4-dibutylthiophene), poly(3-hydroxythiophene), poly(3-methoxythiophene), poly(3-ethoxythiophene), poly(3-butoxythiophene), poly(3-hexyloxythiophene), poly(3-heptyloxythiophene), poly(3-octyloxythiophene), poly(3-decyloxythiophene), poly(3-dodecyloxythiophene), oxythiophene), poly(3-octadecyloxythiophene), poly(3,4-dihydroxythiophene), poly(3,4-dimethoxythiophene), poly(3,4-diethoxythiophene), poly(3,4-dipropoxythiophene), poly(3,4-dibutoxythiophene), poly(3,4-dihexyloxythiophene), poly(3,4-diheptyloxythiophene), poly(3,4-dioctyloxythiophene), poly(3,4-didecyloxythiophene), poly(3,4-di dodecyloxythiophene), poly(3,4-ethylenedioxythiophene), poly(3,4-propylenedioxythiophene), poly(3,4-butylenedioxythiophene), poly(3-methyl-4-methoxythiophene), poly(3-methyl-4-ethoxythiophene), poly(3-carboxythiophene), poly(3-methyl-4-carboxythiophene), poly(3-methyl-4-carboxyethylthiophene), and poly(3-methyl-4-carboxybutylthiophene). Examples of polypyrrole-based conductive polymers include polypyrrole, poly(N-methylpyrrole), poly(3-methylpyrrole), poly(3-ethylpyrrole), poly(3-n-propylpyrrole), poly(3-butylpyrrole), poly(3-octylpyrrole), poly(3-decylpyrrole), poly(3-dodecylpyrrole), poly(3,4-dimethylpyrrole), poly(3,4-dibutylpyrrole), poly(3-carboxypyrrole), poly(3-methyl-4-carboxypyrrole), poly(3-methyl-4-carboxyethylpyrrole), poly(3-methyl-4-carboxybutylpyrrole), poly(3-hydroxypyrrole), poly(3-methoxypyrrole), poly(3-ethoxypyrrole), poly(3-butoxypyrrole), poly(3-hexyloxypyrrole), and poly(3-methyl-4-hexyloxypyrrole). Examples of polyaniline-based conductive polymers include polyaniline, poly(2-methylaniline), poly(3-isobutylaniline), poly(2-anilinesulfonic acid), and poly(3-anilinesulfonic acid). Among these π-conjugated conductive polymers, poly(3,4-ethylenedioxythiophene) is particularly preferable because of its excellent conductivity, transparency, and heat resistance. The conductive composite may contain one type of π-conjugated conductive polymer, or two or more types of polymers.
[0015] (Polyanion) A polyanion is a polymer having two or more monomer units each having an anionic group in the molecule. The anionic group of the polyanion functions as a dopant for a π-conjugated conductive polymer, improving the conductivity of the π-conjugated conductive polymer. The anion group of the polyanion is preferably a sulfo group or a carboxy group. Specific examples of such polyanions include polymers having a sulfo group, such as polystyrene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyacrylic acid esters having a sulfo group, polymethacrylic acid esters having a sulfo group (for example, poly(4-sulfobutyl methacrylate, polysulfoethyl methacrylate, polymethacryloyloxybenzenesulfonic acid), poly(2-acrylamido-2-methylpropanesulfonic acid), and polyisoprene sulfonic acid; and polymers having a carboxy group, such as polyvinyl carboxylic acid, polystyrene carboxylic acid, polyallyl carboxylic acid, polyacrylic acid, polymethacrylic acid, poly(2-acrylamido-2-methylpropanecarboxylic acid), and polyisoprene carboxylic acid. The polyanion may be a homopolymer in which a single monomer is polymerized, or a copolymer in which two or more monomers are polymerized. Among these polyanions, polymers having a sulfo group are preferred, and polystyrene sulfonic acid is more preferred, since they can provide higher electrical conductivity.
[0016] The weight average molecular weight Mw of the polyanion is not particularly limited and is, for example, preferably from 10,000 to 1,000,000, more preferably from 50,000 to 800,000, and even more preferably from 100,000 to 600,000. When the weight average molecular weight Mw of the polyanion is within the above range, the viscosity of the conductive complex dispersion of this embodiment becomes appropriately low, and a capacitor with a sufficiently low ESR can be easily produced. The weight average molecular weight Mw of the polyanion is measured by gel filtration chromatography and is the average molecular weight based on mass calculated in terms of pullulan.
[0017] The content of the polyanion contained in the conductive composite dispersion of this embodiment is, for example, preferably in the range of 1 part by mass to 1000 parts by mass, more preferably 10 parts by mass to 700 parts by mass, and even more preferably 100 parts by mass to 500 parts by mass, relative to 100 parts by mass of the π-conjugated conductive polymer. If the content of the polyanion is equal to or greater than the lower limit, the doping effect on the π-conjugated conductive polymer tends to be stronger, and the conductivity becomes higher. On the other hand, if the content of the polyanion is equal to or less than the upper limit, the π-conjugated conductive polymer can be sufficiently contained, so that sufficient conductivity can be ensured.
[0018] The content of the conductive complex in the conductive complex dispersion of this embodiment is preferably 0.1 parts by mass or more and 3.0 parts by mass or less, more preferably 0.5 parts by mass or more and 2.5 parts by mass or less, even more preferably 1.0 parts by mass or more and 2.3 parts by mass or less, and most preferably 1.3 parts by mass or more and 2.0 parts by mass or less, relative to 100 parts by mass of the conductive complex (the total of the π-conjugated conductive polymer and the polyanion) and water. When the content is at least the lower limit of the above range, the conductivity of the cured product of the conductive composite dispersion is further increased. When it is equal to or less than the upper limit of the above range, the viscosity of the conductive complex dispersion can be easily reduced.
[0019] The content of the conductive complex (the total content of the π-conjugated conductive polymer and the polyanion) relative to the total mass of the conductive complex dispersion of this embodiment is, for example, preferably 0.1 mass% or more and 2.5 mass% or less, more preferably 0.5 mass% or more and 2.0 mass% or less, and even more preferably 1.0 mass% or more and 1.8 mass% or less. When the content is at least the lower limit of the above range, the conductivity of the cured product of the conductive composite dispersion is further increased. When it is equal to or less than the upper limit of the above range, the viscosity of the conductive complex dispersion can be easily reduced.
[0020] (Sugar alcohol) The conductive composite dispersion of this embodiment contains a specific sugar alcohol. By containing the specific sugar alcohol together with the polymer compound described below, the conductivity after curing can be improved, and the capacitor performance can be improved (capacitance, ESR, and withstand voltage can be improved).
[0021] From the viewpoint of fully obtaining the above-mentioned effects, the sugar alcohol preferably has 4 to 7 carbon atoms and 3 to 7 hydroxyl groups in the sugar alcohol molecule, more preferably has a non-cyclic structure, and further preferably is one or more selected from pentaerythritol, sorbitol, mannitol, and erythritol.
[0022] The conductive composite dispersion of this embodiment may contain glucose instead of or together with the sugar alcohol. By containing glucose together with the polymer compound described below, the conductivity after curing is improved, and the capacitor performance can be improved (capacitance, heat resistance of ESR, and withstand voltage are improved).
[0023] In the conductive composite dispersion of this embodiment, the mass ratio A / B of the content A of the sugar alcohol and glucose to the content B of the polymer compound described below is preferably 0.3 or more and less than 1.5, more preferably 0.4 or more and 1.4 or less, even more preferably 0.4 or more and 1.3 or less, particularly preferably 0.5 or more and 1.2 or less, and most preferably 0.5 or more and 1.1 or less. When the A / B ratio is equal to or greater than the lower limit, the capacitance and heat resistance of the ESR of the capacitor are improved, whereas when the A / B ratio is equal to or less than the upper limit, the withstand voltage of the capacitor is improved.
[0024] The total content of the sugar alcohol and glucose in the conductive complex dispersion liquid of this embodiment is preferably 50 parts by mass or more and 1,500 parts by mass or less, more preferably 100 parts by mass or more and 1,200 parts by mass or less, even more preferably 200 parts by mass or more and 900 parts by mass or less, and most preferably 300 parts by mass or more and 700 parts by mass or less, relative to 100 parts by mass of the conductive complex (the total of the π-conjugated conductive polymer and the polyanion). When it is equal to or more than the lower limit of the above range, the capacitance and heat resistance of the ESR of the capacitor can be further improved, and when it is equal to or less than the upper limit of the above range, the withstand voltage of the capacitor can be further improved.
[0025] The total content of the sugar alcohol and glucose relative to the total mass of the conductive composite dispersion of this embodiment is, for example, preferably 0.1 mass% or more and 20 mass% or less, more preferably 1.0 mass% or more and 15.0 mass% or less, even more preferably 3.0 mass% or more and 12.0 mass% or less, and most preferably 6.0 mass% or more and 10.0 mass% or less. When it is equal to or more than the lower limit of the above range, the capacitance and heat resistance of the ESR of the capacitor can be further improved, and when it is equal to or less than the upper limit of the above range, the withstand voltage of the capacitor can be further improved.
[0026] (polymer compound) The conductive complex dispersion of this embodiment preferably contains one or more polymer compounds different from the conductive complex (i.e., polymer compounds different from the π-conjugated conductive polymer and the polyanion). In consideration of dispersibility in water, the polymer compound is preferably a water-soluble polymer. From the viewpoint of suppressing an increase in viscosity, the average molecular weight of the polymer compound is preferably 2000 or less, more preferably 1500 or less, and even more preferably 1000 or less. The lower limit of the average molecular weight is preferably 200 or more. Specifically, for example, it is preferable to contain at least one of polyethylene glycol (PEG) and polypropylene glycol (PPG).
[0027] The content of the polymer compound in the conductive complex dispersion of this embodiment is preferably 50 parts by mass or more and 1,500 parts by mass or less, more preferably 100 parts by mass or more and 1,200 parts by mass or less, still more preferably 150 parts by mass or more and 900 parts by mass or less, and most preferably 200 parts by mass or more and 600 parts by mass or less, relative to 100 parts by mass of the conductive complex (the total of the π-conjugated conductive polymer and the polyanion). When the content is equal to or greater than the lower limit of the above range, the withstand voltage of the capacitor can be further improved, and when the content is equal to or less than the upper limit of the above range, the decrease in the heat resistance of the capacitance and ESR of the capacitor can be sufficiently suppressed.
[0028] The content of the polymer compound relative to the total mass of the conductive composite dispersion of this embodiment is, for example, preferably 0.1 mass% or more and 20 mass% or less, more preferably 1.0 mass% or more and 15.0 mass% or less, even more preferably 2.0 mass% or more and 12.0 mass% or less, and most preferably 3.0 mass% or more and 9.0 mass% or less. When the content is equal to or greater than the lower limit of the above range, the withstand voltage of the capacitor can be further improved, and when the content is equal to or less than the upper limit of the above range, the decrease in the heat resistance of the capacitance and ESR of the capacitor can be sufficiently suppressed.
[0029] (dispersion medium) The dispersion medium contained in the conductive composite dispersion liquid is preferably an aqueous dispersion medium containing water because the conductive composite is hydrophilic. Also, a dispersion medium other than water may be contained. The dispersion medium other than water is not particularly limited as long as it does not significantly impair the dispersibility of the conductive composite. Since the conductive complex has excess anion groups derived from polyanions and has high dispersibility in water, the dispersion medium other than water is preferably a water-soluble organic solvent. Here, the water-soluble organic solvent is an organic solvent that dissolves in an amount of 1 g or more in 100 g of water at 20°C, and examples of such organic solvents include alcohol-based solvents, ketone-based solvents, and ester-based solvents. The water-soluble organic solvent contained as the dispersion medium may be one type or two or more types. Note that the non-water-soluble organic solvent is an organic solvent that dissolves in an amount of less than 1 g.
[0030] The content of water relative to the total mass of the conductive complex dispersion is preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 75% by mass or more. Also, it is preferably 99% by mass or less. When the conductive complex dispersion contains water in an amount equal to or more than the above lower limit, the dispersibility of the conductive complex contained in the conductive complex dispersion is increased, and the performance of a capacitor having a solid electrolyte layer formed from the conductive complex dispersion can be further improved. Also, the conductivity of the conductive layer formed from the conductive complex dispersion can be further improved.
[0031] (Neutralizer) The conductive complex dispersion of this embodiment may further contain one or more neutralizing agents. When the polyanion has an acid group, the conductive complex dispersion tends to become strongly acidic, but this can be neutralized by a neutralizing agent. Examples of the neutralizing agent include basic compounds. The basic compound functions as a Bronsted base that accepts protons from the excess anion groups of the polyanion. In order to fulfill this function, the amount of the basic compound dissolved in water is preferably 0.001 g or more per 100 g of water at 20° C. The upper limit of the amount dissolved is not particularly limited, but even if it is about 0.1 g, the above function can be fulfilled sufficiently.
[0032] Examples of the basic compound that can be used include organic or inorganic basic compounds containing nitrogen, hydroxides of alkali metals or Group 2 metals, various carbonates and hydrogen carbonates, etc. Examples include hydroxides of alkali metals, quaternary ammonium hydroxides or salts thereof, ammonia, amines, etc. Specific examples of the alkali metal hydroxide include potassium hydroxide and sodium hydroxide. Specific examples of carbonates or hydrogen carbonates include ammonium hydrogen carbonate, ammonium carbonate, potassium hydrogen carbonate, potassium carbonate, sodium hydrogen carbonate, and sodium carbonate. Specific examples of the quaternary ammonium hydroxide or a salt thereof include tetramethylammonium hydroxide, tetraethylammonium hydroxide, and tetrabutylammonium hydroxide.
[0033] Examples of the amine include aliphatic tertiary amines and nitrogen-containing aromatic compounds. Examples of the aliphatic tertiary amine include triethanolamine, trimethylamine, triethylamine, tripropylamine, tributylamine, trihexylamine, trioctylamine, triphenylamine, tribenzylamine, and trinaphthylamine.
[0034] Examples of nitrogen-containing aromatic compounds (aromatic compounds in which at least one nitrogen atom forms a ring structure) include pyrrole, indole, imidazole, 2-methylimidazole, 2-propylimidazole, N-methylimidazole, N-propylimidazole, N-butylimidazole, 1-(2-hydroxyethyl)imidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 1-benzyl-2-methylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, and 1-cyanoethyl-2-ethyl-4-methylimidazole. Examples of the aryloxy group include 2-phenyl-4,5-dihydroxymethylimidazole, 1-acetylimidazole, 2-aminobenzimidazole, 2-amino-1-methylbenzimidazole, 2-hydroxybenzimidazole, 2-(2-pyridyl)benzimidazole, pyridine, pyrimidine, pyrazine, and derivatives thereof such as alkyl-substituted products (e.g., substituted with an alkyl group having 1 to 4 carbon atoms, such as methyl, ethyl, propyl, or butyl), halogen-substituted products (e.g., substituted with a halogen group, such as fluoro, chloro, or bromine), and nitrile-substituted products. Of these, nitrogen-containing aromatic compounds are preferred, and imidazole is more preferred.
[0035] The content of the basic compound contained in the conductive complex dispersion liquid is, for example, preferably 1 part by mass or more and 100 parts by mass or less, more preferably 5 parts by mass or more and 60 parts by mass or less, and even more preferably 10 parts by mass or more and 30 parts by mass or less, relative to 100 parts by mass of the conductive complex (total of the π-conjugated conductive polymer and the polyanion). When it is in the above suitable range, the acidity of the conductive complex dispersion liquid is weakened, the corrosiveness to the substrate is reduced, and the ESR of the capacitor can be further reduced.
[0036] The content of the basic compound contained in the conductive composite dispersion is preferably such that the pH of the conductive composite dispersion (25°C) is 2.0 to 8.0, more preferably 2.0 to 5.0, and even more preferably 2.0 to 3.0. Within the above preferred range, the ESR of the capacitor can be further reduced.
[0037] (High boiling point solvent) The conductive composite dispersion of this embodiment may further contain one or more organic solvents (high boiling point solvents) having a boiling point of 150° C. or higher at 1 atmosphere (101,325 Pascals). The boiling point is preferably 250° C. or lower. By including a high boiling point solvent, the effect of improving the conductivity of the cured product of the conductive composite dispersion can be obtained.
[0038] Examples of high boiling point solvents include water-soluble organic solvents and water-insoluble organic solvents, the definitions of which are the same as those described above.
[0039] Examples of the high-boiling water-soluble organic solvent include alcohol-based solvents, ether-based solvents, ketone-based solvents, nitrogen atom-containing solvents, and sulfur atom-containing solvents. Examples of alcohol-based solvents include polyhydric alcohols such as ethylene glycol (boiling point 198°C), 1,2-propanediol (also known as propylene glycol, boiling point 188°C), 1,3-propanediol (boiling point 214°C), 1,2-butanediol (boiling point 194°C), 1,3-butanediol (boiling point 207°C), 1,4-butanediol (boiling point 228°C), dipropylene glycol (boiling point 232°C, mixture of isomers), and diethylene glycol (boiling point 245°C). Examples of ether solvents include diethylene glycol dimethyl ether (boiling point 162° C.) and diethylene glycol diethyl ether (boiling point 188° C.). Examples of ketone solvents include methyl amyl ketone (boiling point 151° C.) and diacetone alcohol (boiling point 168° C.). Examples of nitrogen atom-containing solvents include N-methylpyrrolidone (boiling point 202° C.), N-methylacetamide (boiling point 206° C.), dimethylacetamide (boiling point 165° C.), and N,N-dimethylformamide (boiling point 153° C.). An example of the sulfur atom-containing solvent is dimethyl sulfoxide (boiling point: 189° C.).
[0040] Examples of the high-boiling point water-insoluble organic solvent include hydrocarbon solvents, etc. Examples of the hydrocarbon solvent include aliphatic hydrocarbon solvents and aromatic hydrocarbon solvents. Examples of the aliphatic hydrocarbon solvent include nonane (boiling point 151° C.), decane (boiling point 174° C.), and dodecane (boiling point 216° C.). Examples of aromatic hydrocarbon solvents include propylbenzene (boiling point 159° C.) and isopropylbenzene (boiling point 152° C.).
[0041] Among the above examples, alcohol-based high boiling point solvents are preferred because they provide a greater effect of improving electrical conductivity. Among the alcohol-based high-boiling point solvents, ethylene glycol (boiling point 198°C), 1,2-propanediol (boiling point 188°C), 1,3-propanediol (boiling point 214°C), diethylene glycol (boiling point 245°C), and dimethyl sulfoxide (boiling point 189°C) are preferred because of their excellent effects in improving conductivity, etc.
[0042] The content of the high-boiling point solvent contained in the conductive composite dispersion liquid is, for example, preferably 10 parts by mass or more and 2000 parts by mass or less, more preferably 100 parts by mass or more and 1000 parts by mass or less, and even more preferably 400 parts by mass or more and 800 parts by mass or less, relative to 100 parts by mass of the conductive composite (the total of the π-conjugated conductive polymer and the polyanion). Within the above range, the ESR of a capacitor having a solid electrolyte layer formed from the conductive composite dispersion can be further reduced, and the conductivity of the conductive layer formed from the conductive composite dispersion can be further increased.
[0043] The content of the high-boiling point solvent relative to the total mass of the conductive polymer-containing liquid of this embodiment is, for example, preferably 0.1 mass% or more and 20 mass% or less, more preferably 1.0 mass% or more and 18.0 mass% or less, even more preferably 3.0 mass% or more and 15.0 mass% or less, and most preferably 6.0 mass% or more and 12.0 mass% or less. When the content is at least the lower limit of the above range, the ESR and electrical conductivity can be further improved. When it is equal to or less than the upper limit of the above range, an increase in the viscosity of the conductive complex dispersion can be suppressed.
[0044] (Optional Additives) The conductive composite dispersion may contain other optional additives. The content ratio is appropriately determined depending on the type of additive, but can be, for example, 1 to 1000 parts by mass per 100 parts by mass of the total of the π-conjugated conductive polymer and the polyanion. Here, the optional additives are compounds other than the basic compound, the high boiling point solvent, the sugar alcohol, the polymer compound, and the dispersion medium.
[0045] Examples of the optional additives include a surfactant, an inorganic conductive agent, an antifoaming agent, a coupling agent, an antioxidant, and an ultraviolet absorbing agent. The surfactant may be a nonionic, anionic or cationic surfactant, with the nonionic surfactant being preferred from the standpoint of storage stability. A polymer surfactant such as polyvinyl alcohol may also be added. Examples of the inorganic conductive agent include metal ions, conductive carbon, etc. Metal ions can be generated by dissolving a metal salt in water. The antifoaming agent includes silicone resin, polydimethylsiloxane, silicone oil, and the like. The coupling agent may be a silane coupling agent having a vinyl group, an amino group, an epoxy group, or the like. Examples of the antioxidant include phenol-based antioxidants, amine-based antioxidants, phosphorus-based antioxidants, sulfur-based antioxidants, and sugars. Examples of the ultraviolet absorber include benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, salicylate-based ultraviolet absorbers, cyanoacrylate-based ultraviolet absorbers, oxanilide-based ultraviolet absorbers, hindered amine-based ultraviolet absorbers, and benzoate-based ultraviolet absorbers.
[0046] <Method for producing conductive composite dispersion> As a method for producing the conductive composite dispersion of the first aspect of the present invention, for example, a method of adding a sugar alcohol or glucose, the polymer compound, and, if necessary, a neutralizing agent and a high boiling point solvent to an aqueous dispersion of a conductive composite can be mentioned. The blending of each component can be as desired, and it is preferable to blend them so as to be within the above-mentioned preferred range. The aqueous dispersion of the conductive complex may be obtained by chemically oxidizing and polymerizing a monomer that forms a π-conjugated conductive polymer in an aqueous solution of a polyanion by a known method, or a commercially available product may be used.
[0047] <Capacitor manufacturing method> A capacitor can be manufactured by a manufacturing method including a step of applying the conductive composite dispersion of the first embodiment to the surface of a dielectric layer formed on the surface of an anode made of a porous valve metal, and drying the applied conductive composite dispersion to form a solid electrolyte layer.
[0048] The method for manufacturing a capacitor preferably includes a step of oxidizing the surface of an anode made of a porous valve metal to form a dielectric layer (dielectric forming step), a step of arranging a cathode in a position facing the dielectric layer (cathode forming step), and a step of forming a solid electrolyte layer on at least a part of the surface of the dielectric layer (film forming step). Each step will be described below with reference to FIG.
[0049] [Dielectric formation process] In this step, the surface of anode 11 made of a porous valve metal is oxidized to form dielectric layer 12. The method for forming dielectric layer 12 is not particularly limited, and examples thereof include a method in which the surface of anode 11 is anodized in an electrolyte for chemical conversion treatment, such as an aqueous solution of ammonium adipate, an aqueous solution of ammonium borate, or an aqueous solution of ammonium phosphate.
[0050] [Cathode formation process] In this step, the cathode 13 is disposed at a position facing the dielectric layer 12. The method for disposing the cathode 13 is not particularly limited, and examples thereof include a method of forming the cathode 13 using a conductive paste such as a carbon paste or a silver paste, and a method of disposing a metal foil such as an aluminum foil facing the dielectric layer 12.
[0051] [Film forming process] In this step, the above-mentioned conductive complex dispersion liquid is applied to at least a portion of the surface of the dielectric layer 12, and then dried to form the solid electrolyte layer 14.
[0052] Examples of the method for applying the conductive complex dispersion include immersion (dip coating), comma coating, reverse coating, lip coating, and microgravure coating. Among these, a method in which the anode 11 is immersed in the conductive complex dispersion under reduced pressure is preferred. The immersion method allows the conductive complex dispersion to be sufficiently applied even to the inside of the porous structure on the surface of the dielectric layer 12. After immersion, the anode is taken out and subjected to the next drying treatment.
[0053] Examples of the drying method include room temperature drying, hot air drying, far infrared drying, etc. Among these, hot air drying is preferred. The drying temperature is, for example, preferably 100 to 180° C., and more preferably 120 to 150° C. The drying time is, for example, preferably 0.2 to 1 hour. After drying, the capacitor can be assembled in the usual manner.
[0054] The composition of the components contained in the solid electrolyte layer 14 reflects the composition of the applied conductive composite dispersion liquid. The total content of the sugar alcohol and glucose relative to 100 parts by mass of the conductive complex (the total of the π-conjugated conductive polymer and the polyanion) contained in the solid electrolyte layer 14 is, for example, preferably 50 parts by mass or more and 1500 parts by mass or less, more preferably 100 parts by mass or more and 1200 parts by mass or less, even more preferably 200 parts by mass or more and 900 parts by mass or less, and most preferably 300 parts by mass or more and 700 parts by mass or less. When it is equal to or more than the lower limit of the above range, the capacitance and heat resistance of the ESR of the capacitor can be further improved, and when it is equal to or less than the upper limit of the above range, the withstand voltage of the capacitor can be further improved.
[0055] The content of the polymer compound relative to 100 parts by mass of the conductive complex (the total of the π-conjugated conductive polymer and the polyanion) contained in the solid electrolyte layer 14 is, for example, preferably 50 parts by mass or more and 1500 parts by mass or less, more preferably 100 parts by mass or more and 1200 parts by mass or less, even more preferably 150 parts by mass or more and 900 parts by mass or less, and most preferably 200 parts by mass or more and 600 parts by mass or less. When the content is equal to or greater than the lower limit of the above range, the withstand voltage of the capacitor can be further improved, and when the content is equal to or less than the upper limit of the above range, the decrease in the heat resistance of the capacitance and ESR of the capacitor can be sufficiently suppressed.
[0056] <Capacitor> The capacitor comprises an anode made of a porous body of a valve metal, a dielectric layer made of an oxide of the valve metal, a cathode made of a conductive material provided on the dielectric layer opposite the anode, and a solid electrolyte layer formed between the dielectric layer and the cathode, and the solid electrolyte layer contains a cured product of the conductive composite dispersion of the first aspect.
[0057] An example of an embodiment of the capacitor will be described with reference to Fig. 1. A capacitor 10 shown in Fig. 1 includes an anode 11 made of a porous body of a valve metal, a dielectric layer 12 made of an oxide of the valve metal, a solid electrolyte layer 14 formed on the surface of the dielectric layer 12, and a cathode 13 provided on the outermost side. The cathode 13 is provided on the opposite side to the anode 11, with the dielectric layer 12 and the solid electrolyte layer 14 sandwiched therebetween.
[0058] Examples of valve metals constituting the anode 11 include aluminum, tantalum, niobium, titanium, hafnium, zirconium, zinc, tungsten, bismuth, and antimony. Among these, aluminum, tantalum, and niobium are preferable. Specific examples of the anode 11 include an aluminum foil that has been etched to increase its surface area and then oxidized, and a tantalum or niobium particle sintered body that has been oxidized and pelletized. Such a processed body is a porous body with irregularities on the surface.
[0059] The dielectric layer 12 in this embodiment is a layer formed by oxidizing the surface of the anode 11, for example, by anodizing the surface of the metallic anode 11 in an electrolyte such as an aqueous solution of ammonium adipate. Similar to the anode 11, the dielectric layer 12 also has projections and recesses.
[0060] The cathode 13 in this embodiment may be a conductive layer formed from a conductive paste or a metal layer made of a conductive material such as aluminum foil.
[0061] The solid electrolyte layer 14 in this embodiment is formed on the surface of the dielectric layer 12. The solid electrolyte layer 14 covers at least a portion of the surface of the dielectric layer 12, and may cover the entire surface of the dielectric layer 12. The thickness of the solid electrolyte layer 14 may be constant or may not be constant, and may be, for example, between 1 μm and 100 μm.
[0062] [Electrolyte] The capacitor may have an electrolyte impregnating a solid electrolyte layer. Examples of the solvent constituting the electrolytic solution include alcohol-based solvents such as ethylene glycol, diethylene glycol, propylene glycol, 1,4-butanediol, and glycerin; lactone-based solvents such as γ-butyrolactone, γ-valerolactone, and δ-valerolactone; sulfur-based solvents such as sulfolane, dimethyl sulfoxide, and dimethyl sulfone; amide-based solvents such as N-methylformamide, N,N-dimethylformamide, N-methylacetamide, and N-methylpyrrolidinone; nitrile-based solvents such as acetonitrile and 3-methoxypropionitrile; and water. Examples of the electrolyte constituting the electrolytic solution include organic acids such as adipic acid, glutaric acid, succinic acid, benzoic acid, isophthalic acid, phthalic acid, terephthalic acid, maleic acid, toluic acid, enanthic acid, malonic acid, formic acid, decanedicarboxylic acids such as 1,6-decanedicarboxylic acid and 5,6-decanedicarboxylic acid, octanedicarboxylic acids such as 1,7-octanedicarboxylic acid, azelaic acid, and sebacic acid; or boric acid, a polyhydric alcohol complex compound of boric acid obtained from boric acid and a polyhydric alcohol; inorganic acids such as phosphoric acid, carbonic acid, and silicic acid as anion components, and primary amines (methylamine, ethylamine, propylamine, butylamine, ethylenediamine, etc.), secondary amines (dimethylamine, diethylamine, dipropylamine, methylethylamine, diphenylamine, etc.), tertiary amines (trimethylamine, triethylamine, tripropylamine, triphenylamine, 1,8-diazabicyclo(5,4,0)-undecene-7, etc.), tetraalkylammonium (tetramethylammonium, tetraethylammonium, tetrapropylammonium, tetrabutylammonium, methyltriethylammonium, dimethyldiethylammonium, etc.), etc., as a cationic component.
[0063] The capacitor is not limited to the above configuration, and may have a separator provided between the dielectric layer and the cathode. An example of a capacitor having a separator provided between the dielectric layer and the cathode is a wound type capacitor. Examples of the separator include sheets (including nonwoven fabrics) made of cellulose, polyvinyl alcohol, polyester, polyethylene, polystyrene, polypropylene, polyimide, polyamide, polyvinylidene fluoride, etc., and nonwoven fabrics of glass fibers. The density of the separator is, for example, 0.1 g / cm 3 More than 1.0g / cm 3 The following are included: When a separator is provided, a method of forming a cathode by impregnating the separator with carbon paste or silver paste can also be applied.
[0064] <Method for manufacturing conductive laminate> The conductive laminate can be produced by a production method including a step of applying the conductive composite dispersion according to the first aspect of the present invention to at least a partial surface of a substrate to form a conductive layer.
[0065] Examples of a method for applying (coating) the conductive composite dispersion onto any surface of a substrate include a method using a coater such as a gravure coater, a roll coater, a curtain flow coater, a spin coater, a bar coater, a reverse coater, a kiss coater, a fountain coater, a rod coater, an air doctor coater, a knife coater, a blade coater, a cast coater, or a screen coater; a method using a sprayer such as an air spray, an airless spray, or a rotor dampening; and an immersion method such as dipping.
[0066] The amount of the conductive composite dispersion applied to the substrate is not particularly limited, but may be, for example, 0.01 to 10.0 g / m as a non-volatile component. 2 The range is preferably:
[0067] The coating film made of the conductive complex dispersion applied onto the substrate is dried to remove at least a portion of the dispersion medium, and then cured to form a conductive layer. Methods for drying the coating film include heat drying, vacuum drying, etc. Examples of heat drying that can be used include hot air heating and infrared heating. When applying heat drying, the heating temperature is appropriately set depending on the dispersion medium used, but is usually within the range of 50° C. to 200° C. Here, the heating temperature is the set temperature of the drying device. A suitable drying time within the above heating temperature range is preferably 0.5 minutes to 30 minutes, more preferably 1 minute to 15 minutes.
[0068] <Conductive laminate> The conductive laminate comprises a substrate and a conductive layer formed on at least a portion of the surface of the substrate, and the conductive layer contains a cured product of the conductive composite dispersion of the first aspect.
[0069] [Conductive layer] The conductive layer may be formed over the entire surface of any surface of the substrate, or over a portion of the entire surface. In the conductive film, it is preferable that a conductive layer of substantially uniform thickness is formed over substantially the entire surface of one surface or the other surface of the film substrate. When a conductive layer is formed only over a portion of the surface of the substrate, the conductive layer may be, for example, a fine conductive pattern such as a circuit or an electrode, or the conductive layer may be provided on the same surface and the conductive layer may be not provided on the same surface and may be roughly divided.
[0070] The average thickness of the conductive layer is, for example, preferably 10 nm or more and 100 μm or less, more preferably 20 nm or more and 50 μm or less, and even more preferably 30 nm or more and 30 μm or less. When the average thickness of the conductive layer is equal to or greater than the lower limit, high conductivity can be exhibited, and when the average thickness is equal to or less than the upper limit, the adhesion of the conductive layer to the substrate is further improved.
[0071] The composition of the components contained in the conductive layer reflects the composition of the conductive composite dispersion that is applied. The total content of the sugar alcohol and glucose relative to 100 parts by mass of the conductive complex (the total of the π-conjugated conductive polymer and the polyanion) contained in the conductive layer is, for example, preferably 50 parts by mass or more and 1500 parts by mass or less, more preferably 100 parts by mass or more and 1200 parts by mass or less, even more preferably 200 parts by mass or more and 900 parts by mass or less, and most preferably 300 parts by mass or more and 700 parts by mass or less. When it is in the above range, the conductivity of the conductive layer is good.
[0072] The content of the polymer compound relative to 100 parts by mass of the conductive complex (the total of the π-conjugated conductive polymer and the polyanion) contained in the conductive layer is, for example, preferably 50 parts by mass or more and 1500 parts by mass or less, more preferably 100 parts by mass or more and 1200 parts by mass or less, even more preferably 150 parts by mass or more and 900 parts by mass or less, and most preferably 200 parts by mass or more and 600 parts by mass or less. When the content is within the above range, the conductivity of the conductive layer becomes good.
[0073] [Base material] The substrate may be a substrate made of an insulating material or a substrate made of a conductive material. The shape of the substrate is not particularly limited, and examples thereof include a shape mainly having a flat surface, such as a film or a substrate. Examples of insulating materials include glass, synthetic resin, and ceramics. The conductive material may be a metal, a conductive metal oxide, carbon, or the like.
[0074] (Film substrate) When a film substrate is used as the substrate, the conductive laminate becomes a conductive film. The film substrate may be, for example, a plastic film made of a synthetic resin, such as ethylene-methyl methacrylate copolymer resin, ethylene-vinyl acetate copolymer resin, polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyvinyl alcohol, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyacrylate, polycarbonate, polyvinylidene fluoride, polyarylate, styrene-based elastomer, polyester-based elastomer, polyethersulfone, polyetherimide, polyetheretherketone, polyphenylene sulfide, polyimide, cellulose triacetate, cellulose acetate propionate, etc. From the viewpoint of improving the adhesion between the film substrate and the conductive layer, the synthetic resin for the film substrate is preferably a polyester resin, and among these, polyethylene terephthalate is preferable.
[0075] The synthetic resin for the film substrate may be either amorphous or crystalline. The film substrate may be either unstretched or stretched. The film substrate may be subjected to a surface treatment such as a corona discharge treatment, a plasma treatment, or a flame treatment in order to further improve the adhesion of the conductive layer.
[0076] The average thickness of the film substrate is preferably 5 μm to 500 μm, more preferably 20 μm to 200 μm. If the average thickness of the film substrate is equal to or more than the lower limit, the film is less likely to break, and if the average thickness is equal to or less than the upper limit, the film can have sufficient flexibility. The average thickness of the film substrate is calculated by measuring the thickness at 10 randomly selected points and averaging the measured values.
[0077] (Glass substrate) Examples of the glass substrate include an alkali-free glass substrate, a soda-lime glass substrate, a borosilicate glass substrate, and a quartz glass substrate. If the substrate contains an alkali component, the conductivity of the conductive layer tends to decrease, so among the above glass substrates, an alkali-free glass is preferred. Here, the alkali-free glass refers to a glass composition in which the content of the alkali component is 0.1 mass% or less with respect to the total mass of the glass composition.
[0078] The average thickness of the glass substrate is preferably from 100 μm to 3000 μm, more preferably from 100 μm to 1000 μm. If the average thickness of the glass substrate is equal to or more than the lower limit, the substrate is less likely to break, and if the average thickness is equal to or less than the upper limit, the substrate can contribute to a thinner conductive laminate. The average thickness of the glass substrate is calculated by measuring the thickness at 10 randomly selected points and averaging the measured values. EXAMPLES
[0079] (Production Example 1) Production of polystyrene sulfonic acid 206 g of sodium styrenesulfonate was dissolved in 1000 ml of ion-exchanged water, and while stirring at 80° C., 1.14 g of an oxidizing agent solution of ammonium persulfate previously dissolved in 10 ml of water was added dropwise over 20 minutes, and the solution was stirred for 12 hours. 1000ml of sulfuric acid diluted to 10% by mass was added to the obtained sodium polystyrene sulfonate solution, and about 1000ml of the solvent from the obtained polystyrene sulfonic acid solution was removed by ultrafiltration. Next, 2000ml of ion-exchanged water was added to the remaining liquid, and about 2000ml of the solvent was removed by ultrafiltration to wash the polystyrene sulfonic acid with water. This washing operation was repeated three times. Water in the resulting solution was removed under reduced pressure to obtain colorless solid polystyrene sulfonic acid (PSS).
[0080] (Production Example 2) Production of PEDOT-PSS aqueous dispersion 14.2 g of 3,4-ethylenedioxythiophene and a solution in which 36.7 g of polystyrene sulfonic acid was dissolved in 2000 ml of ion-exchanged water were mixed at 20°C. The resulting mixed solution was kept at 20° C., and while stirring, 29.64 g of ammonium persulfate and 8.0 g of an oxidation catalyst solution of ferric sulfate dissolved in 200 ml of ion-exchanged water were slowly added, followed by stirring for 3 hours to carry out the reaction. To the reaction solution, 2000 ml of ion-exchanged water was added, and about 2000 ml of the solvent was removed by ultrafiltration. This operation was repeated three times. Then, 200 ml of sulfuric acid diluted to 10% by mass and 2000 ml of ion-exchanged water were added to the obtained solution, and about 2000 ml of the solvent was removed by ultrafiltration. 2000 ml of ion-exchanged water was added to the remaining liquid, and about 2000 ml of the solution was removed by ultrafiltration. This operation was repeated three times. Furthermore, 2000 ml of ion-exchanged water was added to the obtained solution, and about 2000 ml of the solvent was removed by ultrafiltration. This operation was repeated five times to obtain a 1.2 mass% polystyrene sulfonate-doped poly(3,4-ethylenedioxythiophene) (PEDOT-PSS aqueous dispersion) solution. Further ultrafiltration was performed to obtain a 2 mass% PEDOT-PSS aqueous dispersion.
[0081] (Production Example 3) Preparation of Capacitor Element After connecting an anode lead terminal to the etched aluminum foil (anode foil), a voltage of 40 V was applied in a 10% by mass aqueous solution of ammonium adipate to perform chemical conversion (oxidation treatment) and form dielectric layers on both sides of the aluminum foil to obtain an anode foil. Next, opposing aluminum cathode foils to which cathode lead terminals were welded were laminated on both sides of the anode foil via a cellulose separator, and the resultant was rolled up into a cylindrical shape to obtain a capacitor element.
[0082] (Production Example 4) 77 g of ethylene glycol, 23 g of polyethylene glycol #300, and 1 g of p-hydroxybenzoic acid were mixed together to obtain a driving electrolyte.
[0083] Example 1 0.4g of imidazole, 10g of diethylene glycol, 10g of sorbitol, and 5g of polyethylene glycol #300 were added to 100g of the PEDOT-PSS aqueous dispersion obtained in Production Example 2, and the mixture was stirred for 30 minutes to obtain a conductive composite dispersion (hereinafter referred to as a coating composition). The coating composition had a pH of 2.5. Next, the capacitor element obtained in Production Example 3 was immersed in a coating composition under reduced pressure, and then dried in a hot air dryer at 125°C / 30 minutes or 180°C / 60 minutes to obtain a capacitor element having a solid electrolyte containing a conductive complex formed on the surface of the dielectric layer. Finally, the capacitor element having the above-mentioned solid electrolyte layer formed thereon and the driving electrolyte solution obtained in Production Example 4 were loaded into an aluminum case, sealed with a sealing rubber, and then treated at 125°C for 30 minutes with an applied voltage of 40 V to produce a capacitor.
[0084] Example 2 A capacitor was fabricated in the same manner as in Example 1, except that polyethylene glycol #300 was changed to polyethylene glycol #600.
[0085] Example 3 A capacitor was fabricated in the same manner as in Example 1, except that polyethylene glycol #300 was changed to polyethylene glycol #1000.
[0086] Example 4 A capacitor was fabricated in the same manner as in Example 1, except that polyethylene glycol #300 was changed to polyethylene glycol #400.
[0087] Example 5 A capacitor was fabricated in the same manner as in Example 1, except that the amount of polyethylene glycol #300 was changed from 5 g to 10 g.
[0088] Example 6 A capacitor was fabricated in the same manner as in Example 5, except that polyethylene glycol #300 was changed to polyethylene glycol #600.
[0089] Example 7 A capacitor was fabricated in the same manner as in Example 5, except that polyethylene glycol #300 was changed to polyethylene glycol #400.
[0090] Example 8 A capacitor was prepared in the same manner as in Example 6, except that sorbitol was changed to mannitol.
[0091] Example 9 A capacitor was produced in the same manner as in Example 6, except that sorbitol was changed to erythritol.
[0092] Example 10 A capacitor was produced in the same manner as in Example 6, except that sorbitol was changed to pentaerythritol.
[0093] Example 11 A capacitor was produced in the same manner as in Example 6, except that sorbitol was changed to glucose.
[0094] Comparative Example 1 A capacitor was fabricated in the same manner as in Example 1, except that sorbitol was changed to mannitol and 5 g of polyethylene glycol #300 was changed to 15 g of polyethylene glycol #600.
[0095] Comparative Example 2 A capacitor was fabricated in the same manner as in Example 1, except that polyethylene glycol #300 was not added.
[0096] Comparative Example 3 A capacitor was fabricated in the same manner as in Comparative Example 2, except that sorbitol was changed to erythritol.
[0097] [pH measurement] The pH was measured at 25°C by a conventional method using a commercially available pH meter.
[0098] [Measurement of capacitance and equivalent series resistance] The capacitance (unit: μF) at 120 Hz and the equivalent series resistance (ESR) (unit: mΩ) at 100 kHz of the capacitors prepared using the conductive composite dispersions of each example were measured using an LCR meter ZM2376 (NF Corporation). The ESR measurement results are shown in Table 1.
[0099] [Measurement of withstand voltage] At room temperature, the voltage of the prepared capacitor was increased from 16 V at a rate of 1 V / sec using a DC power supply, and the voltage value when the current value reached 3 mA was measured as the withstand voltage (unit: V). The results are shown in Table 1.
[0100] [Table 1]
[0101] From the above, the conductive composite dispersion produced in the examples of the present invention contains sugar alcohol or glucose at a specific mass ratio relative to the polymer compound such as PEG or PPG, so the performance of the produced capacitor is excellent. In particular, the balance between the heat resistance related to ESR or capacitance and the withstand voltage is excellent. On the other hand, the conductive complex dispersion liquid of Comparative Example 1 had a high sugar alcohol content and therefore had low heat resistance. The conductive complex dispersion liquids of Comparative Examples 2 and 3 did not contain polymer compounds such as PEG or PPG and therefore had low voltage resistance. [Explanation of symbols]
[0102] 10 Capacitor 11 Anode 12 Dielectric layer 13 Cathode 14 Solid electrolyte layer
Claims
1. The conductive complex includes a π-conjugated conductive polymer and a polyanion, water, a sugar alcohol or glucose having 4 to 7 carbon atoms and 3 to 7 hydroxyl groups in the molecule, and a polymer compound different from the conductive complex; The conductive complex dispersion has a mass ratio, expressed as A / B, of the content A of the sugar alcohol and glucose to the content B of the polymer compound, of 0.3 or more and less than 1.
5.
2. The conductive complex dispersion according to claim 1 , wherein the sugar alcohol comprises at least one of sorbitol, mannitol, erythritol, and pentaerythritol.
3. The conductive composite dispersion according to claim 2 , wherein the polymer compound contains at least one of polyethylene glycol and polypropylene glycol.
4. The conductive composite dispersion according to claim 3 , further comprising an organic solvent having a boiling point of 150° C. or higher at 1 atmospheric pressure.
5. The π-conjugated conductive polymer is poly(3,4-ethylenedioxythiophene), or the polyanion is polystyrenesulfonic acid, or 5. The conductive composite dispersion according to claim 4, wherein the π-conjugated conductive polymer is poly(3,4-ethylenedioxythiophene) and the polyanion is polystyrenesulfonic acid.
6. A method for producing a conductive complex dispersion, comprising: mixing a conductive complex consisting of a π-conjugated conductive polymer and a polyanion, water, a sugar alcohol or glucose having 4 to 7 carbon atoms in the molecule and 3 to 7 hydroxyl groups, and a polymer compound different from the conductive complex, to obtain a conductive complex dispersion in which a mass ratio, expressed as A / B, of a content A of the sugar alcohol and glucose to a content B of the polymer compound is 0.3 or more and less than 1.
5.
7. The present invention relates to a valve metal porous body, and a cathode made of a conductive material and provided on the dielectric layer opposite to the anode. A capacitor, wherein the solid electrolyte layer is a cured product of the conductive composite dispersion according to any one of claims 1 to 5.
8. A method for producing a capacitor, comprising the steps of applying the conductive composite dispersion liquid according to any one of claims 1 to 5 to a surface of a dielectric layer formed on a surface of an anode made of a porous body of a valve metal, and drying the applied conductive composite dispersion liquid to form a solid electrolyte.
9. A substrate and a conductive layer formed on at least a portion of the surface of the substrate, A conductive laminate, wherein the conductive layer is a cured product of the conductive composite dispersion according to any one of claims 1 to 5.
10. A method for producing a conductive laminate, comprising a step of applying the conductive composite dispersion liquid according to any one of claims 1 to 5 to at least a part of a surface of a substrate, and drying the applied coating liquid to form a conductive layer.
Citation Information
Patent Citations
Capacitor and method of manufacturing the same
JP2011171674A
Capacitor and method of manufacturing the same
JP2011171675A
Capacitor and manufacturing method thereof
JP2022071400A